Beliefs about Mathematics and Mathematics Assessment in Post-Secondary Education - Milica Videnovic (Universitas Tidar, 2022)
This paper studied the beliefs about mathematics, mathematics assessment, and written and oral mathematics assessment in post-secondary education from the mathematics professors’ perspectives. Seven mathematics professors and instructors were interviewed and asked to explain how they perceive mathematics and mathematics assessment and how they compare the oral exam to the written exam. Four out of seven mathematics professors and instructors were educated in Poland, Romania, Bosnia, and Ukraine, and they are currently teaching mathematics at a university in Canada. The other three professors were educated in Canada, Germany, and the United States, and they are currently teaching at a university in Germany. Five participants had previously experienced an oral examination in mathematics, while the other two had never been exposed to an oral examination in mathematics throughout their schooling. The results showed that similar beliefs about mathematics and mathematics assessment result in different beliefs about written and oral mathematics assessment.